2016
DOI: 10.1158/1538-7445.sabcs15-p6-03-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-03-05: Cell-free DNA as molecular tool for monitoring disease progression and response to therapy in breast cancer patients

Abstract: Background: Identification of cancer-specific genes from breast cancer cells was instrumental in the advancement of targeted breast cancer therapy. However, with genomic heterogeneity within the breast cancer and evolution of cancer over time, genomic sequencing obtained from a single biopsy site may not capture the complete genomic profile. Thus, circulating cell-free DNA (cfDNA), isolated from plasma, is potentially a non-invasive source of identifying cancer-specific genomic alterations and may provide comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Madic et al, 2015 also demonstrated 81% concordant results between the two types of biopsies [ 48 ]. Later, 50% discordances for TP53 mutations were found by different authors [ 40 ], [ 50 ], and lower concordant results (36.4% and 22%) were reported by Chae et al, 2017 [ 51 ] and Rodriguez et al, 2019 [ 44 ], respectively. Finally, Delmonico et al, 2019 found no concordance for TP53 mutations in paired cfDNA/tissue samples [ 46 ].…”
Section: Variability Of Tp53 Status Between Liquid and Solid Biopsmentioning
confidence: 92%
See 1 more Smart Citation
“…Madic et al, 2015 also demonstrated 81% concordant results between the two types of biopsies [ 48 ]. Later, 50% discordances for TP53 mutations were found by different authors [ 40 ], [ 50 ], and lower concordant results (36.4% and 22%) were reported by Chae et al, 2017 [ 51 ] and Rodriguez et al, 2019 [ 44 ], respectively. Finally, Delmonico et al, 2019 found no concordance for TP53 mutations in paired cfDNA/tissue samples [ 46 ].…”
Section: Variability Of Tp53 Status Between Liquid and Solid Biopsmentioning
confidence: 92%
“…Regarding breast cancer treatment, presence of TP53 mutations in cfDNA is associated with lower progression-free survival [ 50 ] independently of treatment, and increasing VAFs are associated with treatment resistance [ 69 ] and metastatic events [ 70 ]. Li et al, 2017 demonstrated that the mutant TP53 protein sensitizes to some biological therapies such as Lapatinib [ 71 ].…”
Section: Clinical Utility Of Tp53 Mutation Idenmentioning
confidence: 99%